p53: An Attractive Therapeutic Target for Cancer - Patel, Krupa R.; Patel, Hitesh D. (Current Medicinal Chemistry, 2020)
Cancer is a leading cause of death worldwide. It initiates when cell cycle regulatory genes lose their function either by environmental and/or by internal factors. Tumor suppressor protein p53, known as “Guardian of genome”, plays a central role in maintaining genomic stability of the cell. Mutation of TP53 is documented in more than 50% of human cancers, usually by overexpression of negative regulator protein MDM2. Hence, reactivation of p53 by blocking the protein-protein interaction between the murine double minute 2 (MDM2) and the tumor suppressor protein p53 has become the most promising therapeutic strategy in oncology. Several classes of small molecules have been identified as potent, selective and efficient p53-MDM2 inhibitors. Herein, we review the druggability of p53-MDM2 inhibitors and their optimization approaches as well as clinical candidates categorized by scaffold type.
Keywords: p53 reactivation